(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The advertisement is a form of marketing communication which is used to encourage, convince or manipulate an audience (the viewers, listeners or readers, sometimes a special group) to take or to continue taking some actions. Advertisements have an important role in increasing sales. Successful ads that result with the growth of sales require competent personnel including a number of specialists therefore it is very necessary to choose the personnel carefully, to ensure firms a stable position in the market. Advertisement costs are quite large, but they have to be in accordance with the growth of sales.Advertising is one of the marketing strategies to promote products to consumers. Many advertising are available offering interesting advertising packages. Media plays an important role in displaying the good and the bad to the audience. The emergence of new technologies and the demand from audience has internationalized local media. This paper focuses on the role of advertisement in sales. Advertising and sales promotion are considered as the main tools of marketing communication which is influential in attracting the attention of the customer and building brand equity. Advertising and sales promotions are highly effective in affecting consumer purchase decisions of a particular brand.